Improving PMSM Control Based on Optimizing the Output Membership Function of Fuzzy PI Controller with Weighted Modified Jaya Algorithm - Khanh, Pham Quoc; Anh, Ho Pham Huy; Thuyen, Chau Minh (Universitas Muhammadiyah Yogyakarta, 2025)
Electric vehicle manufacturers prefer permanent magnet synchronous motors for their drive systems because of their high efficiency and power density. PI controllers are ineffective in variable speed drives because they are only linearized to operate within a specific range. One of the solutions applied is to use fuzzy PI controllers instead of PI controllers. When using fuzzy controllers, the designer must be able to adjust the controller parameters to ensure the required control efficiency. There are many ways to improve the control quality of a fuzzy PI controller, such as changing the fuzzification and defuzzification coefficients, the fuzzy rules, the type of membership function, and the shape of the output membership function. In this paper, the method of changing the shape of the output membership function of the speed controller based on the fuzzy PI controller is used to improve the speed control quality of the PMSM motor. The Jaya algorithm and its variants have proven effective in recent publications. In this paper, the Jaya algorithm is supplemented with hybrid weights when targeting the best and worst values in the proposed population to determine the optimal shape of the output membership function implemented by the proposed weighted modified Jaya optimization algorithm. Experimental results on the physical model show the effectiveness of improving the quality of motor speed control when applying the proposed optimization algorithm compared with the basic fuzzy controller based on error assessment criteria such as integral time absolute error (ITAE), integral square error (ISE), and integral absolute error (IAE).